Peran Generasi Muda sebagai Pelopor Toleransi dalam Program Moderasi Beragama: Kajian Literatur di Kota Pekalongan - Zahrotul Milatina; Nindi Aulia; Azzahra Nabila; Alma Khorina; Muhamad Masrur (CV. KAMPUS AKADEMIK PUBLISING, 2025)
To maintain social harmony, the values of tolerance and religious moderation are reinforced in Indonesia, which is rich in religious, ethnic, and cultural diversity. The purpose of this study is to examine how the younger generation teaches tolerance through religious moderation programs in the city of Pekalongan, which is famous for its multiculturalism and religiosity. This research uses a library research method with a qualitative descriptive approach. Data was collected from various scientific sources, including books, articles, journals, and related documents. The study shows that the younger generation has a strategic role in promoting the value of moderation through education, social activities, and the use of digital media to foster an inclusive attitude and prevent the spread of intolerance. In Pekalongan, religious moderation has proven to work well thanks to interfaith cooperation, character education, and community empowerment. Strengthening the role of the younger generation is key to creating a harmonious and peaceful social life through an educational, collaborative, and wasathiyah-based approach